Islamic thought in the dialogue of cultures : a historical and bibliographical survey - Daiber, Hans, 1942- (Themes in Islamic Studies, 2012)
Islamic thought is the most beautiful result of a multicultural dialogue. Islamic culture became a bridge between antiquity, Iranian scholars, Syriac and Arabic Christians and the Latin Middle Ages. Its richness of ideas, its plurality of values can contribute to the requirements of modern plurality. The monograph aims at a historical and bibliographical survey of the qurʾānic and rational world-view of early Islam, of the period of translations from Greek into Syriac and Arabic, and of the impact of Islamic thought on the Latin Middle Ages. Critical reflexions of Muslim scholars stimulated new scientific ideas and make us aware of the contribution of Islam to humanity.